Pemantauan Dinamika Tutupan Hutan Dan Pemodelan Spasial Deforestasi di Kawasan Taman Wisata Alam Bangko-Bangko, Pulau Lombok: Forest Cover Dynamics Monitoring and Deforestation Spatial Modeling in Bangko-Bangko Nature Park Area, In Lombok Island - Rizki, Lalu Erkana Ridhan; Idris, Muhamad Husni; Prasetyo, Andrie Ridzki (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
Nature Tourism Park play an important role as conservation areas that support biodiversity conservation while providing nature-based education and recreation spaces for the community. The purpose of this study is to determine changes in forest cover conditions and develop a spatial model of deforestation based on influencing factors in the Bangko-Bangko Nature Park. This study was conducted from February to May 2025 in the Bangko-Bangko Nature Park in Lombok Island. The data used included Sentinel 2A imagery 2020 and 2025, elevation, road networks, river networks, administrative boundaries, and population data. Land cover classification was performed using visual techniques (on-screen digitization). The spatial model of deforestation was constructed using the logistic regression method. The results of the study show that forest cover in the Bangko-Bangko Nature Park has decreased from 1.397 Ha in 2020 to 818 Ha in 2025, or deforestation of 579 Ha, or 115,8 Ha per year. The spatial model of deforestation at the study site follow logit equation: logit deforestation = -0,7759 – 0,002746*elevation – 0,000157*distance from road + 0,000406*distance from settlement – 0.000967*population density – 0,001258*distance from river + 0,019391*slope.